Proceedings of the Tenth Annual ACM/IEEE International Conference on Human-Robot Interaction 2015
DOI: 10.1145/2696454.2696468
|View full text |Cite
|
Sign up to set email alerts
|

Escaping from Children's Abuse of Social Robots

Abstract: Social robots working in public space often stimulate children's curiosity. However, sometimes children also show abusive behavior toward robots. In our case studies, we observed in many cases that children persistently obstruct the robot's activity. Some actually abused the robot by saying bad things, and at times even kicking or punching the robot. We developed a statistical model of occurrence of children's abuse. Using this model together with a simulator of pedestrian behavior, we enabled the robot to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 22 publications
1
63
1
2
Order By: Relevance
“…Whitby (), for example, has argued that it is already time to have an informed debate about the ethical issues that arise with social robots—well before robots become ubiquitous in our daily lives. For example, children will bully and abuse robots in a shopping mall (a) when their parents are not around, (b) when there are few witnesses, and (c) despite pleas from the robot to stop the abuse (Brscić, Kidokoro, Suehiro, & Kanda, ). Abusing a robot may not violate contemporary ethical norms, but it is not difficult to imagine that sometime in the near future those norms will change.…”
Section: Human–robot Interaction and Intergroup Relationsmentioning
confidence: 99%
“…Whitby (), for example, has argued that it is already time to have an informed debate about the ethical issues that arise with social robots—well before robots become ubiquitous in our daily lives. For example, children will bully and abuse robots in a shopping mall (a) when their parents are not around, (b) when there are few witnesses, and (c) despite pleas from the robot to stop the abuse (Brscić, Kidokoro, Suehiro, & Kanda, ). Abusing a robot may not violate contemporary ethical norms, but it is not difficult to imagine that sometime in the near future those norms will change.…”
Section: Human–robot Interaction and Intergroup Relationsmentioning
confidence: 99%
“…e cleaning robot from the Salvini et al [53] study is not alone in being abused; Brscić et al [5] observed how kids a acked a robot that was patrolling a shopping mall. A er multiple failed a empts to design robot behaviour that could stop these aggressive tendencies, the authors had to program the robot in such a way that it simply avoided potential bullies (i.e., any kid-sized human).…”
Section: Introductionmentioning
confidence: 99%
“…However, robots sometimes suffer from abusive behaviors from children and young people [1,2]. Abusive behaviors are also reported for embodied conversational agents [3].…”
Section: Introductionmentioning
confidence: 99%